ANALISA KEPEMIMPINAN DI AMERIKA SERIKAT DAN DI INDONESIA YANG MENGANUT SISTEM DEMOKRASI - Amalia, Renada; Van Graha, Fager; Maharani, Riska; Akbar Alva Rizky, Nabel (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
The countries of Indonesia and the United States also apply the theory of power-sharing which, according to Montesquieu's power-sharing theory, divides government power into three, namely executive, legislative and judicial powers. The United States of America is a federal country that carries out a republican democratic system because people can elect delegates who represent them in the body of government. Indonesia is a developing country that implements democratic systems and principles in the life of the nation. Using research literature from various scientific articles to compile or obtain scientific knowledge. The aim of this research methodology is to produce competent, credible and relevant research that is directly related to the problem under study. Data collection techniques include reading various articles and using secondary and primary data. There are various indicators that distinguish leadership in Indonesia and the United States, from the discussion that has been described it can be concluded that there are differences in leadership in America and Indonesia both using a democratic system.